The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3171/2017.5.jns17831
|View full text |Cite
|
Sign up to set email alerts
|

Dual antiplatelet therapy in aneurysmal subarachnoid hemorrhage: association with reduced risk of clinical vasospasm and delayed cerebral ischemia

Abstract: OBJECTIVE Clinical vasospasm and delayed cerebral ischemia (DCI) are devastating complications of aneurysmal subarachnoid hemorrhage (aSAH). Several theories involving platelet activation have been postulated as potential explanations of the development of clinical vasospasm and DCI. However, the effects of dual antiplatelet therapy (DAPT; aspirin and clopidogrel) on clinical vasospasm and DCI have not been previously investigated. The objective of this study was to evaluate the effects of DAPT on clinical vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
48
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 35 publications
1
48
1
1
Order By: Relevance
“…Ultimately, this may contribute to the pathophysiology of DCI. 35 Based on our results, it seems that increasing fibrin formation and polymerisation might play a role in the pathophysiology of DCI. In clinical setting the antiplatelet therapy has failed to prevent this increased fibrin formation or reduce the incidence of DCI or mortality after aSAH.…”
Section: Vahteramentioning
confidence: 56%
See 1 more Smart Citation
“…Ultimately, this may contribute to the pathophysiology of DCI. 35 Based on our results, it seems that increasing fibrin formation and polymerisation might play a role in the pathophysiology of DCI. In clinical setting the antiplatelet therapy has failed to prevent this increased fibrin formation or reduce the incidence of DCI or mortality after aSAH.…”
Section: Vahteramentioning
confidence: 56%
“…36 Nonetheless, a recent retrospective trial showed promising result when dual antiplatelet therapy was used. 35…”
Section: Vahteramentioning
confidence: 99%
“…A complicação de maior ocorrência neste estudo foi o vasoespasmo arterial (leve, moderado e severo), ocorrendo em 6 dos 26 casos que apresentaram complicação do aneurisma (23,0%). Dado compatível com a literatura que demonstra o mesmo como complicação mais frequente, principalmente entre os HSA por aneurismas rotos 24,25 .…”
Section: Discussionunclassified
“…Vasospasm refers to an abnormal contraction of blood vessels and can cause tissue ischemia or necrosis. At present, research is mainly focused on cerebral vasospasm during subarachnoid hemorrhage and coronary artery spasms . The mechanisms behind these processes are roughly similar, including the activation of protein kinase C, decreased nitric oxide, increased endothelin, intracellular changes in the calcium concentration, activation of inflammatory cells and factors, and structural changes in the spasmodic artery wall .…”
Section: Discussionmentioning
confidence: 99%